Synergistic effect of graphene oxide and silver nanoparticles as biostimulant improves the postharvest life of cut flower bird of paradise (Strelitzia reginae L.) - Thakur, Meenakshi; Chandel, Anjali; Guleria, Shweta; Verma, Vipasha; Kumar, Raghawendra; Singh, Gurpreet; Rakwal, Anjali; Sharma, Diksha; Bhargava, Bhavya (Frontiers in Plant Science, 2022)
The bird of paradise (Strelitzia reginae L.) is one of the important tropical cut flowers. Generally, flowers like bird of paradise (BOP) grown for the commercial ornamental market must be of high pre and postharvest quality. Thus, to improve the postharvest longevity and increase marketability, the relative efficacy of two different biologically synthesized nanoparticles (NPs) was evaluated. The novel proprietary stimulants were graphene oxide (GO) and silver nanoparticles (SNPs). The NP treatments were applied as a vase (lower concentrations) solutions. Among all the applied treatments, the synergistic effect of GO + SNPs at 1 µL L−1 vase solution significantly (p =0.05) prolongs the post-harvest life of cut flowers of BOP. Increased vase life over the deionized water (DI) control was associated with better maintenance of relative water uptake, relative fresh weight, suppressed microbial density at stem-end and delay of stem blockage, reduced electrolyte leakage, malondialdehyde (MDA), SOD, and POD activity. In contrast to control, administration of NPs gave better results for all analyzed parameters. Application of biologically synthesized NPs in combination (GO + SNPs at 1 µL L−1) extended the vase life of cut flowers by 6 days compared with control flowers, and overall, showed better results than the control. The findings of the studies revealed that the standardized NPs could have more potential in prolonging the postharvest life of cut flowers in BOP. Thus, this technique can be used as a novel postharvest technology for commercial application in cut flowers.